Mastering Windows network forensics and investigation - Anson, Steven James (Wiley,John Wiley [distributor], 2007)
This comprehensive guide provides you with the training you need to arm yourself against phishing, bank fraud, unlawful hacking, and other computer crimes. Two seasoned law enforcement professionals discuss everything from recognizing high-tech criminal activity and collecting evidence to presenting it in a way that judges and juries can understand. They cover the range of skills, standards, and step-by-step procedures you’ll need to conduct a criminal investigation in a Windows environment and make your evidence stand up in court